Algumas considerações sobre a poesia de Eucanaã Ferraz - Baldan, Maria de Lourdes Ortiz Gandini [UNESP] (My University, 2011)
The contemporary Brazilian poetic production is marked by a strong diversity in the forms of expression and the thematic contents that it makes circulate; it is found either turned to the critical reading of the Brazilian poetry‟s most traditional repertoire, or more concerned about the research of new expressive models afforded by language. Such constitutive diversity, which operates on the intermediate gradients between these two tendencies, finds itself underlined by the little orthodox practice of the production divulgation and circulation, that appropriated the internet and the poetic performances to compensate the low paper-based edition. What we have is a type of poetic dialectology which identifies the poetry readers group. Verifying the most regular procedures in the construction of the dialectology, through the work of Eucanaã Ferraz and João Cabral, is the objective of this paper.

A produção poética brasileira contemporânea é marcada por uma forte diversidade nas formas de expressão e nos conteúdos temáticos que faz circular; encontra-se ora mais voltada à leitura crítica do repertório mais tradicional da poesia brasileira, ora mais preocupada com a pesquisa de novos modelos expressivos propiciados pela linguagem. Tal diversidade constitutiva, que opera nos gradientes intermediários entre essas duas tendências, vê-se sublinhada pela prática pouco ortodoxa de divulgação e circulação da produção, que se apropriou da internet e das performances poéticas para compensar a baixa publicação em livro. O que temos é uma espécie de dialetologia poética que identifica o grupo de leitores de poesia. Verificar os procedimentos mais regulares na construção dessa dialetologia, por meio da obra de Eucanaã Ferraz e João Cabral é o objetivo deste trabalho.
Some considerations on Eucanaã Ferraz’s poetry
Keywords: Brazilian poetry; semiotics; Roman Jakobson; Eucanaã Ferraz; João Cabral; poesia brasileira; semiótica; Roman Jakobson; Eucanaã Ferraz; João Cabral